Data supporting: 'MDAO method and optimum designs of hybrid-electric civil airliners' - Kang, Le (Cranfield University, 2022)
The data is ready to be shared with readers who read the paper 'MDAO method and optimum designs of hybrid-electric civil airliners', which is published on the 'Journal of Aerospace Engineering'. The data includes validation information as well as case study data in this paper. The paper introduced a design environment appropriate to hybrid-electric civil airliners.
Keywords: MDAO database'; 'Aerospace Engineering'; 'Aircraft Performance and Flight Control Systems'